1996
DOI: 10.1017/s0950268800059148
|View full text |Cite
|
Sign up to set email alerts
|

Problems in the diagnosis of foodborne infection in general practice

Abstract: SUMMARYThe incidence of acute gastroenteritis and self suspected food poisoning in general practice populations was compared with consultation rates in four group practices during a 3-month winter period and a 2-month autumn period. The average monthly consultation rate for acute gastroenteritis and self suspected food poisoning was 0 3 % and 0-06 % respectively. However, over the same period, on average, an estimated 7 % of the practice population per month reported an acute gastroenteritis illness, and 0 7 %… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
27
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 4 publications
(4 reference statements)
7
27
2
Order By: Relevance
“…In this study, 20% of respondents with an acute diarrheal illness reported seeking medical care. This rate is similar to those reported in Australia, Canada, and Ireland (Scallan et al, 2005), but higher than that reported for the Netherlands (de Wit et al, 2000; and England and Wales (Palmer et al, 1996).…”
Section: Discussionsupporting
confidence: 87%
“…In this study, 20% of respondents with an acute diarrheal illness reported seeking medical care. This rate is similar to those reported in Australia, Canada, and Ireland (Scallan et al, 2005), but higher than that reported for the Netherlands (de Wit et al, 2000; and England and Wales (Palmer et al, 1996).…”
Section: Discussionsupporting
confidence: 87%
“…These 4 persons were excluded from this analysis. Thus, the incidence of diarrhea in our control group was 86 cases per 100 person-years, which is in line with previous retrospective studies in the United Kingdom [3][4][5]. Statistical analysis in this study was identical to that used for the larger case-control study: the x 2 test or Fisher's exact test were used for univariable analysis, and logistic regression analysis was used for multivariable analysis [8].…”
supporting
confidence: 69%
“…Such variations in outbreak reports from different jurisdictions highlights that differing effort and experience among surveillance personnel may lead to nonuniformities in outbreak identification and classification. 12,13 Outbreaks of gastroenteritis may be difficult for health authorities to recognise, as illness is often mild and selflimiting.…”
Section: Discussionmentioning
confidence: 99%